2018
DOI: 10.3389/fpsyt.2018.00409
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Measure of Postpartum PTSD: The City Birth Trauma Scale

Abstract: Post-traumatic stress disorder (PTSD) affects 4% of women after birth yet there are very few questionnaire measures of postpartum PTSD that have been validated in this population. In addition, none of the available questionnaires assess postpartum PTSD in accordance with criteria specified in the latest edition of the Diagnostic and Statistical Manual [DSM-5, (1)]. The City Birth Trauma Scale is a 29-item questionnaire developed to measure birth-related PTSD according to DSM-5 criteria of: stressor criteria (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
223
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(252 citation statements)
references
References 24 publications
21
223
0
8
Order By: Relevance
“…These figures are similar that have been reported by the developers of the CityBiTS (mean = 11.7 ± 11.0, % = 7.1). 11 Other studies that have assessed PP-PTSD symptoms have reported figures that range from 3% to 39%. 7,13,14 These rates may have varied widely because the studies used different samples and examined different phases of the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…These figures are similar that have been reported by the developers of the CityBiTS (mean = 11.7 ± 11.0, % = 7.1). 11 Other studies that have assessed PP-PTSD symptoms have reported figures that range from 3% to 39%. 7,13,14 These rates may have varied widely because the studies used different samples and examined different phases of the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…City Birth Trauma Scale (City BiTS; Ayers et al, 2018) consists of 29 items measuring birth-related PTSD according to DSM-5 criteria. City BiTS includes criterion A for the traumatic event (2 items; 0no, 1-yes), frequency of symptoms from B-E criteria over the previous week (20 items; 0 -not at all, 1 -once, 2 -2-4 times, and 3 -5 or more times), , criterion F for the duration of symptoms (1 item; 0less than 1 month, 1 -1-3 months, and 2 -3 months or more), criterion G for distress and impairment (2 items; 0no, 1sometimes, 2yes), and exclusion criteria H (1 item; 0 -no, 1maybe, 2yes).…”
Section: Methodsmentioning
confidence: 99%
“…Also, criterion A was changed so that it is no longer necessary for people to both experience the traumatic event (Criterion A1) and intense negative emotions, such as fear, helplessness, or horror (Criterion A2). The removal of the Criterion A2 in relation to postpartum PTSD resulted in somewhat mixed findings: some studies found more postpartum women fulfilled stressor criteria when A2 was removed (Boorman et al, 2013;Devilly, Gullo, Alcorn, & O'Donovan, 2014) whereas other studies did not find a large difference when A2 was VALIDATION OF THE CITY BITS 4 removed (Ayers, Wright, & Thornton, 2018). Another difference in DSM-5 was the removal of emotional numbing symptoms and the addition of the symptoms of Negative alterations in cognitions and mood (Criterion D).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would be important to test that the positive association between PTSD and prenatal attachment still holds when controlling for treatment status. Nevertheless, the likelihood of study participants having received treatment for PTSD following childbirth is rather small, given the short interval between the two assessment points and the fact that birth trauma is usually undetected and women do not receive timely and adequate treatment (Ayers et al 2018).…”
Section: Discussionmentioning
confidence: 99%